Short communication physicochemical and antioxidant potential of raw unprocessed honey from Malaysian stingless bees - Abu Bakar, Mohd Fadzelly; Sanusi, Shuaibu Babaji; Abu Bakar, Fazleen Izzany; Ong, Jin Cong; Mian, Zakbah (Asian Network for Scientific Information (ANSINET), 2017)
Objective: The current study investigates the physicochemical, phytochemical, nutritional composition and antioxidant activity of raw unprocessed honey produced by two Malaysian stingless bees, Heterotrigona itama and Geniotrigona thoracica collected from different places in the Southern part of Peninsular Malaysia. Materials and Methods: Physicochemical (pH, color) and nutritional compositions (moisture, ash, protein, fat, carbohydrates, minerals) were determined and evaluated using standard methods. Phytochemical contents (flavonoid and phenolic compounds) and antioxidant activites were determined spectrophotometrically. Results: pH of collected honey samples were found to be acidic, ranging from 3.24-3.42, while the colors ranged from 85.34-490.37 mm Pfund (golden to dark amber). The moisture, ash, protein, fat and carbohydrate contents of honey samples ranged from 26.5±0.00 to 31.8±0.00 g/100 g, 0.15±0.01 to 0.67±0.00 g/100 g, 0.016t 0.54 g/100 g, 0.02 to 0.15 g/100 g and 67.12 to 73.26 g/100 g, respectively. The total flavonoid content of honey samples dissolved in distilled water and methanol ranged from 53.81±4.12 mg rutin equivalents kgG1 to 549.05±9.74 mg rutin equivalents kgG1 while total phenolic content in both solvents ranged from 357.14±3.57 mg gallic acid equivalents kgG1 to 520.83±4.49 mg gallic acid equivalents kgG1. The antioxidant activity of this honey displayed superior antioxidant potential and was higher than Manuka honey. Conclusion: Clearly, honey produced by these two stingless bee types in the Southern part of Peninsular Malaysia is a budding functional food and possible nutraceuticals with great potential for use in complementary and alternative medicines.